Comparison of the Antibacterial Effects of Nanosil, Chlorhexidine and Probiotic Mouthwashes on Periodontal Pathogens - Sajedinejad, Neda; Nazemi Salman, Bahareh; Darvish, Shayan (Journal of Dental School, 2018)
Objectives Periodontal diseases are one of the common oral diseases and microbial oral flora is one major factor responsible for it. Elimination of periodontal pathogens is particularly important in managing the periodontal state. This study aimed to assess the antibacterial effects of Nanosil, chlorhexidine (CHX) and probiotic mouthwashes on periodontal pathogens. Methods In this in-vitro study, the bacteria (A. actinomycetemcomitans, P. aeruginosa, K. pneumonia, E. coli, S. aureus, B. cereus, B. subtilis, S. typhimurium, E. coli O-157 and E. coli PTCC 1338) were cultured using specific culture media. Microbial suspension was prepared by dissolving 1 or 2 microbial colonies in tryptic soy broth. Nanosil, CHX and probiotic mouthwashes were added to the wells containing bacterial suspension. Samples were taken from wells showing turbidity and cultured in plates. The minimum inhibitory concentration (MIC) of mouthwashes was determined by repeated measuring of the growth inhibition zones. Kolmogorov-Smirnov test, One-way ANOVA, and Scheffe’s post hoc was used for statistical analysis. Results Probiotic mouthwash had greater antibacterial effects than other mouthwashes and caused larger growth inhibition zones. For S. aureus and S. typhimurium, the mean diameter of the growth inhibition zone was not significant (p>0.05), while for other tested bacteria were significant (p<0.05). Conclusion Probiotic mouthwash decreases the pathogenic oral flora and stabilizes the beneficial flora in oral cavity.